Challenges faced by nursing professors in Distance Learning for undergraduates in the COVID-19 Pandemic (Research, Society and Development, 2022)
The COVID-19 pandemic has caused disruptions and challenges at global levels, and, in this sense, it is included in education in general. Education systems were affected in more than 150 countries, which produced the widespread closure of educational institutions such as schools, colleges and universities. As a result, distance learning had to be used by teachers, in order not to stagnate the progress of the school year. Objective: to know the problems and difficulties of teachers in nursing education in the remote modality for undergraduates during the Pandemic, as well as the strategies to minimize these difficulties. Method: descriptive study with a qualitative approach. The target population consisted of undergraduate nursing professors from a Federal educational institution in the state of Rio de Janeiro, from March to November 2020 and approved under the opinion number 4,617,874. The content analysis was carried out in three phases, according to the perspective of Bardin (2016). Result: From this, two categories emerged: Difficulties to teach remotely in the pandemic period and Methods used to teach in the pandemic period, causing challenges for both teachers and students who had to readjust to the new reality. Final Considerations: the study contributed to a clearer and more comprehensive knowledge about the academic teaching world in the Pandemic period, by addressing the difficulties encountered.